Altered Intrinsic Brain Activity in Patients With Toothache Using the Percent Amplitude of a Fluctuation Method: A Resting-State fMRI Study - Yang, Jun; Shao, Yi; Shen, Yan-Kun; Zhu, Hong-Shui; Li, Bin; Yu, Qiu-Yue; Kang, Min; Xu, San-Hua; Ying, Ping; Ling, Qian; Zou, Jie; Wei, Hong; et al. (Frontiers in Neurology, 2022)
Objective: The percent amplitude of fluctuation (PerAF) technique was utilized to evaluate the neural functions of specific cerebrum areas in patients with chronic toothache (TA). Patients and Methods: An aggregation of 18 TA patients (8 males and 10 females) were included in the study. We also recruited 18 healthy controls (HCs; 8 males and 10 females) aligned for sex, age, and weight. Resting functional magnetic resonance imaging (rs-fMRI) scans were obtained. Then we utilized the PerAF method and a support vector machine (SVM) to analyze the image data and measure neural abnormalities in related cerebrum areas. Receiver operating characteristic (ROC) curve analysis was utilized to appraise the two data sets. Results: The PerAF signals in the right dorsolateral superior frontal gyrus and the right posterior central gyrus of TA sufferers were lower than HC signals. These results may reveal neural dysfunctions in relevant cerebrum regions. We also executed SVM to determine the global accuracy of each sample. Conclusion: TA patients had marked differences in PerAF values in some regions of the cerebrum. Changes in PerAF values represented distinctions in blood oxygen level dependent semaphore intensity, which reflected the overactivity or inactivation of some cerebrum areas in TA sufferers. At the same time, we analyzed the PerAF values of TAs with ROC curve, which can be helpful for the diagnosis of TA severity and subsequent treatment. Our results may help to elucidate the pathological mechanism of chronic TA.